La Babilonia que conocieron los magos en Figuras de Bethlem de Gabriel Miró - Palomo Alepuz, Laura (El Colegio de México, 2019)
In the present paper we will analyse the genetic evolution “III. Riegos.Borsipa. Babilonia”, wich is to be found inserted in the segment “Magos” of anunpublished, fragmentary and almost unknown work by Gabriel Miró: Figuras deBethlem. To this end, we study the three existing drafts of this section, taking intoconsideration the textual organisation, the use of the sources employed in configuratingthe section and the content of the same.